Ion Release from Stainless Steel Brackets Subjected to Tooth Bleaching Treatment - Ahmadreza Sardarian; Fatemeh Abbasi; Maryam Pakniyat Jahromi (Shiraz University of Medical Sciences, 2023)
Statement of the Problem: Tooth discoloration in the form of staining is a common finding during conventional orthodontic treatment. Due to elevated esthetic standards, clinicians in the field of orthodontics are faced with increasing demands by patients to perform bleaching treatments while the appliances are still in place. Though the success of such treatments has been reported in literature, the effect of whitening agents on orthodontic appliances has not been evaluated. Increased ion release following corrosion of orthodontic brackets is considered a health hazard. Purpose: In this study, we measured the amount of ion release from steel brackets under home and office bleaching treatment in order to evaluate the safety of such treatments during orthodontic therapy. Materials and Method: In this experimental study, a total of 120 brackets were randomly divided into 3 groups. The first group was subjected to an office bleaching regimen (hydrogen peroxide 40%). The second group was subjected to a home bleaching treatment (carbamide peroxide 20%). The third group did not receive any bleaching treatment. The specimens of all groups were immersed in artificial saliva and after 30 days, the amount of released chromium, copper, iron, magnesium, and nickel ions was measured and compared using one way ANOVA. Results: The results showed that ion release was significantly different between the three groups (p Value >0.05). For the chromium, iron, magnesium, and Nickel ion release the order was as follows: no bleaching < home bleaching < office bleaching. However, the copper ion release was greater in the group that received home bleaching. Conclusion: Ion release was enhanced when bleaching treatments were performed, with office bleaching having a more significant effect. Although the amounts of released ions were less than those permitted by WHO, we suggest that the clinicians recommend home bleaching for orthodontic patients that are seeking tooth whitening treatment.